Contemporary art in the Federal Republic of Germany : 12 collections of 30 graphics : non-objective concrete constructive. - Herzogenrath, Wulf (Stuttgart : IFA - Institut für Auslandsbeziehungen Stuttgart, 1975)
Baumgarten, Bodo ; Böhm, Hartmut ; Gerstner, Karl ; Girke, Raimund ; Graevenitz, Gerhard von ; Hangen, Heijo ; Wilding, Ludwig ; Kovacs, Attila ; Mahlmann, Max H. ; Mavignier, Almir ; Novosad, Karel ; Rave, Horst ; Uecker, Günther ; Ulrichs, Timm
Biog. [1 p.]
12 collections of 30 graphics. Each will provide a survey of contemporary graphic art in the Federal Republic of Germany in a sequence of exhibitions appearing at regular intervals. They are entitled "Tournee-Ring". (...) Planned and selected in 1974 by Dr. Götz Adriani, (...) Dr. Wulf Herzogenrath (...) Organized by the Institute for Foreign Cultural Relations
Engels
boek
Keywords: Duitsland